The Work of KH Irsyad Djuwaeli in Mathla’ul Anwar (1975-2021): Kiprah KH Irsyad Djuwaeli Dalam Mathla’ul Anwar (1975-2021) - Kusman, Agus; Saepudin, Didin (PT. Student Rihlah Indonesia, 2024)
This article discusses the work of KH Irsyad Djuwaeli in leading the Mathla'ul Anwar organization in Indonesia. The research method used is literature study with a historical approach. The results of the research are that KH Irsyad Djuwaeli is trying to maintain the Mathla'ul Anwar Organization to focus on da'wah, education and social affairs. In the field of education, KH Irsyad Djuwaeli built and rehabilitated existing madrasah buildings, such as building the Mathla'ul Anwar College of Economics and the Mathla'ul Anwar Religious Madrasah Aliyah. In the social sector, KH Irsyad Djuwaeli has a paradise grant program and a foster parent program. In the organizational sector, several autonomous institutions and supporting institutions were established, such as Muslimat Mathla'ul Anwar, Mathla'ul Anwar Young Generation, Mathla'ul Anwar Legal Assistance and Consultation Institute, Cooperative Development Institute, and the Hajj and Umrah Guidance Institute.